Identifikasi Miskonsepsi Siswa pada Materi Asam Basa Menggunakan Instrumen Two-Tier Multiple Choice - Laliyo, Lukman Abdul Rauf; Langi, Riyani; Pikoli, Masrid; Munandar, Haris; Thayban, Thayban; Kurniawati, Erga; Sangkota, Vivi Dia Afrianti (Universitas Negeri Gorontalo, 2023)
This research is a descriptive study, which aims to determine students' misconceptions about acid-base material in class XI SMA Negeri 1 Suwawa. The instrument used is Two-tier multiple choice. The research subjects used were class XI Science at SMA Negeri 1 Suwawa, with a sample size of 66 students. Research data was obtained from students' answers to two-tier multiple choice questions. The data is processed based on student answer patterns, which are then grouped into categories of understanding the concept, misconception 1, misconception 2, and not understanding the concept. The research results showed that students who experienced misconception 1 (MK1) were 14.65%, and misconception 2 (MK2) were 16.23%.